A lateral approach to the feline cerebellar fossa: case report and identification of an external landmark for the tentorium ossium. Issue 4 (April 2020) - Kent, Marc; Glass, Eric N; Schachar, Jordan
Objectives: The aim of this study was to describe the use of an external landmark that defines the attachment of the tentorium ossium for planning a craniectomy to access the cerebellar fossa. The external landmark was defined by a line where the caudal aspect of the convexity of the cranium transitions to a flat surface in the caudal aspect of the temporal fossa. We also aimed to determine if this external landmark was present and readily visualized, and to establish its relationship to the nuchal crest using three-dimensional (3D) volume-rendered CT reconstructions created from cats with normal cranial morphology. Methods: First, a case is presented for the description of an approach in a cat with a meningioma located dorsolateral to the cerebellum. Second, CT studies of five cats with normal cranial morphology were selected. Regions of interest (ROIs) were drawn at the attachment of the tentorium ossium to the cranium and nuchal crest. Three-dimensional reconstructions were developed with colored ROI overlays. The external landmark defined the tentorial attachment on all 3D reconstructions. Additionally, using the postoperative CT of the clinical case described herein, ROIs of the tentorial attachment and nuchal crest along with a third ROI, the craniectomy, were drawn and overlaid on the 3D reconstruction to illustrate the position of the craniectomy in relation to the tentorium ossium attachment and nuchal crest. Results: The use of the external landmark provided for a craniectomy that enabled adequate visualization for excision of a meningioma. On all 3D reconstructions, the external landmark was present and readily visualized. Conclusions and relevance: Between the attachment of the tentorium ossium and nuchal crest exists an area adequately sized for a craniectomy in cats. Clinicians can use an identifiable external landmark on the lateral aspect of the cranium to plan the rostral boundary for a craniectomy to access the cerebellar fossa in cats.